Boosting carbon utilization efficiency for sustainable methanol production from biomass: Techno-economic and environmental analysis - Zhang, Leiyu; Gao, Ruxing; Tang, Zongyue; Zhang, Chundong; Jun, Ki Won; Ki Kim, Seok; Zhao, Tiansheng; Wan, Hui; Guan, Guofeng (Energy Conversion and Management, 2024)
Concerns about depleted fossil fuels and the climate crisis have intensified the interest in producing biomass-derived methanol. However, the traditional biomass-to-methanol (BTM) process suffers from low carbon conversion ability and serious CO2 emissions caused by the water–gas-shift (WGS) unit. In this study, three novel BTM processes coupled with solid oxide electrolysis, methane pyrolysis, and methane chemical looping technologies are proposed to eliminate WGS unit, and the systematic heat integration is considered to achieve energy cascade utilization. Meanwhile, process performances are comprehensively evaluated to compare the technical, economic, and environmental attractiveness of three novel BTM processes. It is found that compared with the original BTM process, three novel processes significantly improve carbon efficiency by 22%. Meanwhile, CO2 emissions are reduced by 60%. Moreover, the application of methane chemical looping technology is more economical, and the associated net production cost decreases by more than 30%. Additionally, the BTM process coupled with solid oxide electrolysis is more environmentally friendly, whereas the process with methane pyrolysis technology is more exergy-efficient. Overall, the integrated processes have significant application prospects for carbon conversion and mitigation ability as well as economic attractiveness.
Keywords: Biomass-to-methanol process; Carbon conversions; Carbon utilization; Chemical looping; CO 2 emission; Methane pyrolysis; Solid oxide; Techno-Economic analysis; Water electrolysis; Water-gas shifts; Biomass-to-methanol process; Chemical looping; Methane pyrolysis; Techno-economic analysis; Water electrolysis